1990
DOI: 10.1063/1.459713
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactivity of iron atoms near room temperature

Abstract: The reactivity of ground state iron atoms with respect to atom transfer and adduct formation reactions with a variety of simple molecules in Ar buffer gas near room temperature has been investigated. Iron atoms are produced by visible multiphoton dissociation of iron pentacarbonyl or ferrocene, and their removal by added gases under pseudo-first-order conditions is monitored by resonance fluorescence excitation at variable time delay following the photolysis pulse. Upper limits for second-order rate constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0
3

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 34 publications
6
69
0
3
Order By: Relevance
“…This conclusion agrees with the experimental finding by Mitchell and Hackett. 10 Further decomposition of q-HFeOH to FeO + H 2 is not likely to occur due to the high barrier at q-TS2. The reverse reaction, FeO + H 2 , is found to have a barrier of 12-13 kcal/mol, which can explain the fact that no reaction was observed between FeO and molecular hydrogen at 320 K in the recent experimental study by Rollason and Plane.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This conclusion agrees with the experimental finding by Mitchell and Hackett. 10 Further decomposition of q-HFeOH to FeO + H 2 is not likely to occur due to the high barrier at q-TS2. The reverse reaction, FeO + H 2 , is found to have a barrier of 12-13 kcal/mol, which can explain the fact that no reaction was observed between FeO and molecular hydrogen at 320 K in the recent experimental study by Rollason and Plane.…”
Section: Resultsmentioning
confidence: 99%
“…16 Annealing to 30 and 50 K gives cyclic FeO 2 . The gas-phase reaction of Fe atoms with water at room temperature was studied by Mitchell and Hackett, 10 who found that the corresponding rate constant is low. However, little information is available about the mechanism of this fundamental reaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there has been a recent surge of activity in gas-phase experimental work on the reactivity of molecules such as H2, CO, NH3 and small alkenes and alkynes toward transition-metal atoms [7,8], dimers [7,9, lo], and clusters [l 11 and on the determination of the binding energies and properties of the complexes formed [ 12-141. Full-geometry optimization of clusters and molecule-cluster complexes are desirable in order to make more meaningful comparisons between theory and experiment.…”
Section: Introductionmentioning
confidence: 99%